PERANCANGAN STRUKTUR MENARA LATTICE UNTUK TURBIN ANGIN DARRIEUS TIPE-H DAYA KECIL - Mongkol, Jericho; Tangkuman, Stenly; Rondonuwu, Irvan (Jurnal Poros Teknik Mesin UNSRAT, 2024)
The structure of the lattice tower is designed to be able to withstand the loads that occur, namely the wind force, and the gravity that occurs in the H-type Darrieus wind turbine. Structural calculations can be carried out by considering all the maximum forces affecting and then analyzing them for each part or structural component. The tower is designed with dimensions t x l x p, namely 2500 mm x 500 mm × 500 mm, 5 angle iron rods, the dimensions of the steel plate are 500 mm long × 500 mm wide × 3 mm thick, with ASTM A36 carbon steel as the material. The stress from the simulation outcomes must be equal to or below the allowable stress value where the allowable stress is 83.3 MPa, the von misses stress is 0.110526 MPa, and the results of the simulation show that the stress value fulfills the design requirements. Angle iron specifications yield with the requirements of ASTM A36 carbon steel with a yield strength (250 MPa). Calculation of checking the von misses stress. Keywords: Tower, Stress, Materials.